Islamic Entrepreneurship Education: Cultivating Santri Independence Through Business Management at Pondok Pesantren Annuqayah Latee Guluk-Guluk - Muktirrahman Muktirrahman; Citra Mulya Sari; Retno Febriyastuti Widyawati (Asian Journal of Law and Islamic Finance, 2025)
This study examines the integration of Islamic entrepreneurship education in cultivating santri independence through business management at Pondok Pesantren Annuqayah Latee (PPA Latee) in Guluk-guluk, Sumenep. Using a qualitative approach with data collected through interviews, observations, and document analysis, this research identifies four primary strategies employed by PPA Latee: independent business development, technical education and skills training, application of Islamic values in business, and direct field practice. Findings reveal that these approaches collectively foster multidimensional independence among santri, enhancing their economic self-sufficiency, decision-making abilities, and leadership capacities. The study documents how PPA Latee's business units—categorized into manufacturing, trading, and services sectors—provide practical learning environments where santri develop entrepreneurial skills while applying Islamic business principles such as amanah (trustworthiness), adl (justice), and maslahah (public interest). Supporting factors include mentoring programs and practice-based curriculum, while challenges encompass financial limitations and regulatory complexities. Based on these findings, a comprehensive model for Islamic entrepreneurship education in pesantren settings is proposed, positioning Islamic values as the foundation with experiential learning as the central mechanism. This research contributes to understanding how traditional Islamic educational institutions can effectively integrate entrepreneurial education while maintaining their core religious mission and provides valuable insights for pesantren seeking to enhance santri independence and economic self-reliance.